Maturity parameters based on saturated and aromatic hydrocarbon of shale deposited in a salt lake: a case study in the Qianjiang depression, Jianghan Basin. (2nd April 2020) - Wang, Zixiang; Wei, Zhifu; Zheng, Youheng; Tang, Youjun; Sun, Lina
Abstract: The saturated and aromatic hydrocarbon maturity parameters of shale from a salt lake basin were studied. The results show that the most familiar maturity parameters such as tricyclic terpane/hopane, Ts/Tm, sterane 20S/(20S + 20R), ββ/(ββ + αα), MPI1, MPI2, MPI3, PAI-1, and triaromatic steroid (І)/triaromatic steroid (І+ІІ), are not applicable for oil and source rock from saline lakes. The ratio of methyldibenzothiophene increases with depth, and could be an effective parameter of equivalent vitrinite reflectance. Therefore, caution should be taken when evaluating the maturation of oil or/and source rock from a saline sedimentary basin by maturity parameters based on saturated and aromatic hydrocarbons.